The Utilization of Language Laboratories in Istima’ Learning at Darul ‘Ulum Islamic University Lamongan - Evy Nur Rohmawaty; Abdul Muntaqim Al Anshory; Nur Hasaniyah; M Sholih Salimul Uqba; Khoirotun Ni'mah (Yayasan Sagita Akademia Maju, 2024)
Language laboratories are considered an effective medium for foreign language learning, facilitating teachers and learners to study more effectively. The modern language laboratories used today represent a new and innovative approach, incorporating various types of media with specific functions. This study aims to analyze the use of language laboratories for Istima' learning, the different tools available in language laboratories, students' perceptions of using language laboratories in Istima' learning, and the challenges or obstacles encountered during the use of language laboratories in Istima' learning. The research was conducted at Darul ‘Ulum Islamic University Lamongan. A qualitative descriptive method was used in this study. Data collection techniques included interviews and questionnaires. The findings of this study indicate that: 1) The tools used in the language laboratory for Istima' learning include earphones, LCD screens, projectors, the internet, Wi-Fi, YouTube, and e-learning platforms; 2) The utilization of language laboratories, media, and learning resources is primarily for delivering content and for evaluation or assignments in Istima' learning; 3) Students' perspectives indicate that the media and learning resources used in the language laboratory positively impact their enthusiasm and engagement in Istima' learning.